ANALISIS KEBIJAKAN KURIKULUM UNTUK MENINGKATKAN MUTU PENDIDIKAN DI ERA DIGITALISASI MASYARAKAT 5.0 - Hartini, Tri; Suparmi; Riskawaty, Helyna; Majid, Abdul; Suriansyah, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the form, direction, role, as well as the challenges and opportunities of curriculum policy in improving the quality of education in the digitalization era of Society 5.0. The focus of this study is based on the current educational needs that demand integration between technology and character development in order to prepare students with 21st-century competencies. This research employs a descriptive qualitative approach and was conducted at SMP Negeri 2 Pamukan Selatan. Data were collected through observation, semi-structured interviews, and documentation. The sampling techniques used were purposive sampling and snowball sampling, with research subjects including the principal, teachers, and students.The results show that curriculum policy has begun to be directed toward digital and character-based learning, although its implementation still faces various challenges, such as limited technological infrastructure, teacher preparedness, and students’ access to digital devices. Nevertheless, the policy holds great potential to enhance educational quality, particularly in terms of fostering students’ creativity, collaboration, and digital literacy. In the local context, the school has made several efforts to adapt the curriculum in alignment with the vision of Society 5.0, such as the use of digital media in learning, project-based approaches, and the reinforcement of character values within the school environment. Therefore, curriculum policy needs to be continuously evaluated and strengthened with support from various stakeholders in order to create a responsive, high-quality, and sustainable education system.